Ligustrazine reduces blood-brain barrier permeability in a rat model of focal cerebral ischemia and reperfusion - TAN, FENG (Exp Ther Med, 2015)
Ligustrazine, also known as 2,3,5,6-tetramethylpyrazine (TMP), one of the major active compounds of Ligusticum wallichii Franchat., has been shown to reduce neuroinflammation and protect neurons during cerebral ischemia/reperfusion injury. However, whether it reduces blood-brain barrier (BBB) permeability during ischemic stroke is unclear. The aim of the present study was to investigate the role that TMP plays in protecting the BBB integrity in ischemia/reperfusion injury and to investigate the relevant mechanisms involved. Rats received an intraperitoneal injection of 20 mg/kg TMP 15 min before the onset of ischemia, which was induced by middle cerebral artery occlusion. Infarct volume, neurological score, brain edema, BBB permeability and tight junction protein impairment were observed. The results showed that TMP reduced the neurological score and levels of brain infarction and edema. In addition, TMP significantly decreased BBB permeability and prevented the impairment of occludin and claudin-5, two tight junction protein components of the BBB, in rat brains with ischemia/reperfusion injury. In addition, the expression and activity of matrix metalloproteinases, enzymes responsible for the degradation of the extracellular matrix and tight junctions, were reduced in the rat brains by TMP treatment. These results combined suggest that TMP reduces BBB permeability as well as neuronal damage in focal cerebral ischemia/reperfusion injury in rats.